Associations With Smoking and Shared Epitope Differ Between IgA‐ and IgG‐Class Antibodies to Cyclic Citrullinated Peptides in Early Rheumatoid Arthritis. Issue 8 (28th July 2015) - Svärd, Anna; Skogh, Thomas; Alfredsson, Lars; Ilar, Anna; Klareskog, Lars; Bengtsson, Camilla; Kastbom, Alf
<x xml:space="preserve">Abstract</x> Objective Smoking and HLA–DRB1/shared epitope (SE) alleles are risk factors for rheumatoid arthritis (RA) characterized by seropositivity for antibodies targeting citrullinated proteins (ACPAs)/cyclic citrullinated peptides (anti‐CCP). Previously, mainly IgG‐class antibodies have been studied. IgA‐class antibodies are to a great extent related to mucosal immunity. The aim of this study was to explore interrelations between cigarette smoking, presence of SE, and seropositivity for circulating IgA and/or IgG anti‐CCP antibodies among patients with early RA, to determine whether ACPAs of the IgA subclass are regulated by different mechanisms than those of the IgG subclass. Methods Two cohorts of patients with early RA, from the first Epidemiological Investigations of RA trial (n = 1, 663) and the second Early Intervention in RA trial (n = 199), were grouped into 4 subsets based on anti‐CCP subclass status (IgG−/IgA−, IgG−/IgA+, IgG+/IgA−, and IgG+/IgA+), and each subset was compared with regard to associations with smoking (current and former) and presence of SE. Interaction between smoking and SE was calculated using the attributable proportion (AP) due to interaction (assessing deviation from additivity of effects). Results Smoking was overrepresented among IgA anti‐CCP–positive RA patients, regardless of whether IgG anti‐CCP were present, whereas in patients with IgG anti‐CCP alone, no association with smoking was found. SE alleles were overrepresented among IgG anti‐CCP–positive patients, regardless of IgA anti‐CCP status, and was not seen in patients with IgA anti‐CCP alone. An interaction between ever smoking and SE was found with regard to the risk of IgG+/IgA+ RA (AP 0.5, 95% confidence interval 0.4, 0.6). No significant interaction was observed with regard to the risk of IgG−/IgA+ RA or IgG+/IgA− RA. Conclusion In patients with RA, a history of ever smoking was associated with seropositivity for IgA anti‐CCP antibodies, whereas presence of SE was associated with seropositivity for IgG anti‐CCP antibodies. An interaction between ever smoking and the SE was limited to the RA subset characterized by seropositivity for both IgG and IgA anti‐CCP. These findings provide novel evidence that anti‐CCP–positive RA can be divided into at least 3 serologically distinct subsets associated with different risk factors, indicating different modes of pathogenesis in RA.